2003
DOI: 10.1590/s0104-66322003000300012
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of aromatic amino acids in a fixed bed column

Abstract: Phenylalanine (Phe) and tyrosine (Tyr) are two of the twenty amino acids in proteins; they are classified as aromatic amino acids, because both have a benzene ring in their structures. These amino acids are important in the synthesis of several biologically active amines, such as beta-endorphin, a neurotransmitter. Amino acids can be separated by ion-exchange chromatography. In this case, it is important that fixed-bed adsorber design adequately predict the breakthrough curve. This work presents a mathematical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…In order to obtain this mathematical model, some assumptions are fixed: the flow rate is constant; the transversal cross section is constant for and through the column; radial dispersion is negligible; the axial dispersion coefficient is a function of solute and flow rate; the external mass transfer resistance is considered; the solids are made of spherical particles with uniform radius; the solution is dilute and thus adsorption isotherm is linear; and the pore diffusion model describes the intra-particle transport mechanism. These assumptions were applied to the description of the breakthrough curve (Cremasco et al, 2003), the model of which is summarized in Table 1. In the condition (8), C in is the solute concentration in the flow entering the column.…”
Section: Theorymentioning
confidence: 99%
See 3 more Smart Citations
“…In order to obtain this mathematical model, some assumptions are fixed: the flow rate is constant; the transversal cross section is constant for and through the column; radial dispersion is negligible; the axial dispersion coefficient is a function of solute and flow rate; the external mass transfer resistance is considered; the solids are made of spherical particles with uniform radius; the solution is dilute and thus adsorption isotherm is linear; and the pore diffusion model describes the intra-particle transport mechanism. These assumptions were applied to the description of the breakthrough curve (Cremasco et al, 2003), the model of which is summarized in Table 1. In the condition (8), C in is the solute concentration in the flow entering the column.…”
Section: Theorymentioning
confidence: 99%
“…The intra-particle liquid solute concentration is found analytically and correlated to the liquid bed concentration through Duhamel's theorem. The use of this theorem results in an equation connecting the intraparticle liquid concentration, C p , to the liquid bed concentration, C. This method is described in Cremasco et al (2003).…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…An adsorption process evolution was computationally determined for a system containing compound mixture, using a hybrid method. Based on Cremasco et al (2003), the liquid concentration inside the particles was found analytically and it was related with the liquid bed concentration using Duhamel's theorem. The solution for the liquid bed concentration was found numerically, instead of analytically.…”
Section: Introductionmentioning
confidence: 99%